Experimental and Numerical Investigation of Failure Characteristics and Mechanism of Granites with Different Joint Angles. (18th November 2021) - Wang, Zhenhua; Fang, Jun; Wang, Gang; Jiang, Yifan; Li, Dongwei
Abstract : The uniaxial compression tests were conducted on granite samples with different joint dip angles to more favorably explore the influences of the nonconsecutive joint on mechanical properties and deformation characteristics of the rock mass. The stress-strain curves, deformation and strength characteristics, and energy evolution process of the samples were analyzed. Numerical simulation using particle flow code (PFC) is employed to study the crack propagation process. The mode of jointed and fractured rock was investigated. The research results showed a significant reduction in both the peak strength and elastic modulus of jointed samples compared with intact ones: the peak strength and elastic modulus drop to the minimum at the joint dip angle of about 45°, especially for the peak strength, which takes up about 55% of the intact samples. The fractured samples' total energy, elastic strain energy, and dissipated energy during the uniaxial compression drop significantly relative to intact samples. The proportion of the fracture modes varies with different joint dip angles, in which the ratio of shear cracks grows at first and then declines, with the highest balance at the dip angle of 45°. The damage stress's sensitivity to the dip angle change is greater than that of the peak stress, with reduction amplitude more extensive than the latter.